2019
DOI: 10.1161/str.50.suppl_1.wp363
|View full text |Cite
|
Sign up to set email alerts
|

Abstract WP363: Females are Significantly Less Likely to be Invited as Speakers to the International Stroke Conference: Time’s Up to Address Sex Disparity

Abstract: Introduction: Females are underrepresented as speakers at major scientific conferences. Furthermore, in neurology, males outnumber females in academic positions, rank and number of publications, which may influence this inequality. Objective: To evaluate trends in invited speakers by sex at the International Stroke Conference (ISC). Methods: Data were obtained (years 2014-2018) for invited speakers to the IS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…We further examined the gender distribution of PIs in acute versus non-acute stroke trials prompted by results of a recent investigation that revealed significant differences in gender composition of invited speakers at the International Stroke Conference. 14 We classified acute versus nonacute stroke trials based on the methodology of this publication (Table S1) but also incorporated the time frame of the intervention with any intervention being performed within 24 hours considered as acute.…”
Section: Methodsmentioning
confidence: 99%
“…We further examined the gender distribution of PIs in acute versus non-acute stroke trials prompted by results of a recent investigation that revealed significant differences in gender composition of invited speakers at the International Stroke Conference. 14 We classified acute versus nonacute stroke trials based on the methodology of this publication (Table S1) but also incorporated the time frame of the intervention with any intervention being performed within 24 hours considered as acute.…”
Section: Methodsmentioning
confidence: 99%
“…Neurodisparity is defined as the effect of disparities in neurologic care; [3] it does not only refer to barriers contributed by race and/or ethnicity, but includes disparities influenced by: sex, gender [7], age, neurodiversity, sexual orientation, religion, geographic origin, disability, weight, incarceration, and other social demographic factors [3]. For example, several publications highlight disparities in representation in the American Academy of Neurology recognition awards and of women in leadership roles in neurology [5,6]. Neurocritical care, as a burgeoning discipline, is ripe to lead initiatives to increase awareness of knowledge gaps that will address the needs of diverse patient populations and foster adequate representation in clinical leadership and the neuroscience workforce.…”
Section: Phases Of Team Science [8 9]mentioning
confidence: 99%
“…High-impact translational research is essential for the development of novel therapeutic approaches in neurocritical care. Although it is well known that diversity improves productivity in team science [1][2][3][4], there is still a prominent imbalance in the representation of diverse backgrounds and gender in the neuroscience workforce [5][6][7] and in scientific conferences [6,8]. "The Neurotherapeutics Symposium 2019-Neurological Emergencies" was designed to address these challenges by creating a platform to facilitate the discussion of innovative translational approaches in acute neurologic illnesses, while specifically seeking the participation of women and under represented minorities in the conference planning and development processes.…”
Section: Introductionmentioning
confidence: 99%
“…The number of original papers, which is an important indicator for evaluating performance such as promotion, was also lower for women physicians than for men physicians, which may make promotion difficult for women physicians 4,5 . In addition, opportunities for women physicians to present and gain recognition at academic meetings are limited, and obtaining grants is difficult 6,7 . The percentage of women presenting at academic meetings is also low; in fact, the number of women first presenters at orthopedic meetings has remained consistently low (11.6% in 2017) 8 …”
Section: Introductionmentioning
confidence: 99%